PEKERJAAN SOSIAL SEBAGAI PROFESI INTERNASIONAL: PELUANG DAN TANTANGAN - Yusra Kilun (Jurnal Kommunity Online, 2020)
AbstractThe list of experiences in social development and social welfare throughout history was initiated by King Hammurabi in Babylon. He issued the Code of Justice in 1750, which included a requirement that one helped another during difficult time (Baker, 1995).  A more modern book, written by E. Richmond, entitled “Friendship Visit in the Circle of the Poor” (1899/1969).  One year after publication, he received respond from a figure of education, Simon N, Pattern, questioning the terminology of “social worker” whether the main role of social worker to be advocacy  (social services) is individual or not. The subsequent dialogue during this century focused on whether the social worker was a full profession or semi-profession (Hugman, 1996).As a new approach, what are the challenges and opportunities for the social worker from international perspective? The title focuses on the role of the International Federation Social Worker (IFSW) and the perspective related with the program for the development of social work in the future, and the United Nations (UN) is the main initiatorof international cooperation and social development program.Keywords: social worker; social development; globalisationAbstrakDaftar pengalaman dalam pembangunan sosial dan kesejahteraan sosial sepajang sejarah dimulai dengan King Hammurabi di Babilonia. Dia memunculkan Kode Keadilan pada tahun 1750, yang mencakup suatu persyaratan bahwa seseorang mambantu yang lain selama masa sulit (Barker, 1995). Buku yang  lebih modern lagi adalah buku yang ditulis oleh E. Richmond, dengan judul  “Kunjungan Persahabatan di kalangan Du’afa” (1899/1969). Setahun setelah publikasi, dia mendapatkan tanggapan dari seorang tokoh pendidikan Simon N, Patten yang menanyakan terminology “pekerja sosial”  apakah peran utama pekerja sosial menjadi advokasi atau pelayanan sosial yang bersifat individu atau tidak. Dialog berikutnya selama abad ini fokus pada apakah pekerjaan sosial suatu profesi atau semi profesi (Hugman, 1996).Sebagai suatu pendekatan baru, apa saja tantangan dan peluang bagi profesi pekerja sosial dari perspektif internasional? Judul ini fokus pada peran Federasi Internasional Pekerja Sosial (International Federation Sosial Worker or IFSW) dan perspektifnya tentang program untuk pembangunan pekerjaan sosial di masa mendatang dan PBB (United Nations) sebagai penggagas utama kerjasama internasional dan program pembangunan sosial.Kata kunci: Pekerja sosial; pembangunan sosial; globalisasiAbstractThe list of experiences in social development and social welfare throughout history was initiated by King Hammurabi in Babylon. He issued the Code of Justice in 1750, which included a requirement that one helped another during difficult time (Baker, 1995).  A more modern book, written by E. Richmond, entitled “Friendship Visit in the Circle of the Poor” (1899/1969).  One year after publication, he received respond from a figure of education, Simon N, Pattern, questioning the terminology of “social worker” whether the main role of social worker to be advocacy  (social services) is individual or not. The subsequent dialogue during this century focused on whether the social worker was a full profession or semi-profession (Hugman, 1996).As a new approach, what are the challenges and opportunities for the social worker from international perspective? The title focuses on the role of the International Federation Social Worker (IFSW) and the perspective related with the program for the development of social work in the future, and the United Nations (UN) is the main initiatorof international cooperation and social development program.Keywords: social worker; social development; globalisationAbstrakDaftar pengalaman dalam pembangunan sosial dan kesejahteraan sosial sepajang sejarah dimulai dengan King Hammurabi di Babilonia. Dia memunculkan Kode Keadilan pada tahun 1750, yang mencakup suatu persyaratan bahwa seseorang mambantu yang lain selama masa sulit (Barker, 1995). Buku yang  lebih modern lagi adalah buku yang ditulis oleh E. Richmond, dengan judul  “Kunjungan Persahabatan di kalangan Du’afa” (1899/1969). Setahun setelah publikasi, dia mendapatkan tanggapan dari seorang tokoh pendidikan Simon N, Patten yang menanyakan terminology “pekerja sosial”  apakah peran utama pekerja sosial menjadi advokasi atau pelayanan sosial yang bersifat individu atau tidak. Dialog berikutnya selama abad ini fokus pada apakah pekerjaan sosial suatu profesi atau semi profesi (Hugman, 1996).Sebagai suatu pendekatan baru, apa saja tantangan dan peluang bagi profesi pekerja sosial dari perspektif internasional? Judul ini fokus pada peran Federasi Internasional Pekerja Sosial (International Federation Sosial Worker or IFSW) dan perspektifnya tentang program untuk pembangunan pekerjaan sosial di masa mendatang dan PBB (United Nations) sebagai penggagas utama kerjasama internasional dan program pembangunan sosial.Kata kunci: Pekerja sosial; pembangunan sosial; globalisasiDOI-